Incidence, risk factors, natural history and outcomes of heart failure in patients with Graves' disease. Issue 11 (6th September 2021) - Naser, Jwan A; Pislaru, Sorin; Stan, Marius N; Lin, Grace
Abstract : Objective: Graves' disease (GD) can both aggravate pre-existing cardiac disease and cause de novo heart failure (HF), but large-scale studies are lacking. We aimed to investigate the incidence, risk factors and outcomes of incident GD-related HF. Methods: Patients with GD (2009–2019) were retrospectively included. HF with reduced ejection fraction (HFrEF) was defined by left ventricular ejection fraction <50% and Framingham criteria, while HF with preserved ejection fraction (HFpEF) was defined according to the HFA-PEFF criteria. HF due to ischaemia, valve disorder or other structural heart disease was excluded. Proportional hazards regression was used to analyse risk factors and outcomes. Results: Of 1371 patients with GD, HF occurred in 74 (5.4%) patients (31 (2.3%) HFrEF; 43 (3.1%) HFpEF). In HFrEF, atrial fibrillation (AF) (HR 10.5 (3.0–37.3), p<0.001) and thyrotropin receptor antibody (TRAb) level (HR 1.05 (1.01–1.09) per unit, p=0.007) were independent risk factors. In HFpEF, the independent risk factors were chronic obstructive pulmonary disease (HR 7.2 (3.5–14.6), p<0.001), older age (HR 1.5 (1.2–2.0) per 10 years, p=0.001), overt hyperthyroidism (HR 6.4 (1.5–27.1), p=0.01), higher body mass index (BMI) (HR 1.07 (1.03–1.10) per unit, p=0.001) and hypertension (HR 3.1 (1.3–7.2), p=0.008). The risk of cardiovascular hospitalisations was higher in both HFrEF (HR 10.3 (5.5–19.4), p<0.001) and HFpEF (HR 6.7 (3.7–12.2), p<0.001). However, only HFrEF was associated with an increased risk of all-cause mortality (HR 5.17 (1.3–19.9), p=0.02) and ventricular tachycardia/fibrillation (HR 64.3 (15.9–259.7), p<0.001). Conclusion: De novo HF occurs in 5.4% of patients with GD and is associated with increased risk of cardiovascular hospitalisations and mortality. Risk factors include AF, higher TRAb, higher BMI and overt hyperthyroidism.